Improvement in survivorship: The key for population recovery? - Grandi, Maria Florencia (2016)
In northern Patagonia, commercial harvesting of South American sea lions, Otaria flavescens, from 1920 to 1960, decimated its population abundance. Population recovery was not immediate after hunting ceased in 1962. The population was stable until 1989, and since then has grown at an annual rate of increase of 5.7%. Along with this growth there was an increase of the juvenile fraction and changes in the social composition of colonies, which could be related to changes in some population vital rates. The aim of this study was to analyze changes in the survivorship pattern of Otaria flavescens through time. The ultimate goal was to contribute to a better understanding of changes that could have operated on the ecosystem after the decline and recovery of one of the main marine top-predators in the southern South Atlantic Ocean. The comparisons of survivorship curves of males and females, obtained from the life tables of two periods with different population trends: 1981-1987 (stationary) and 2000-2008 (recovering), showed that there were differences in survivorship between sexes, where recent female age-specific survival was higher than that of males at any age. The comparison of survivorship between periods showed differences in both sexes. Both juveniles and adults, both male and female, from the recent period showed higher survival than those of the 1980’s decade. This improvement in survivorship could be one of the essential factors that drove population recovery in the last decades. Here we discuss the possible hypotheses of which factors could have changed in the ecosystem to favour juvenile and adult survivorship, such as an increase in the availability of food recourses, a decrease of exogenous mortality causes, or a combination of both factors.